2020
DOI: 10.1177/1557988320943359
|View full text |Cite
|
Sign up to set email alerts
|

Confidence in Understanding Health Insurance and Challenges Paying Medical Bills Among Men in the United States

Abstract: Although the number of men with health insurance has increased, men are less likely to utilize health services than females, and experience difficulty in paying medical bills. Understanding the details of health insurance can be challenging and the lack of understanding can have financial consequences. This study, guided by Andersen’s model of health-care utilization, assessed the relationship between confidence level in understanding health insurance terms and difficulty in paying medical bills among American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…14 To date, there is only one validated measure of health insurance literacy, the Health Insurance Literacy Measure (HILM). 8,15 Researchers have documented negative outcomes associated with poor health insurance literacy, such as delaying or avoiding care, 15,16 difficulty paying medical bills 17,18 and reporting difficulty in paying for non-medical needs (e.g., rent, food). 19 National data suggest that 53.8% of US adults have low health insurance literacy based on the HILM (defined as having a score of ≤60 out of 84), 20 suggesting opportunities for improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 To date, there is only one validated measure of health insurance literacy, the Health Insurance Literacy Measure (HILM). 8,15 Researchers have documented negative outcomes associated with poor health insurance literacy, such as delaying or avoiding care, 15,16 difficulty paying medical bills 17,18 and reporting difficulty in paying for non-medical needs (e.g., rent, food). 19 National data suggest that 53.8% of US adults have low health insurance literacy based on the HILM (defined as having a score of ≤60 out of 84), 20 suggesting opportunities for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Health insurance literacy is defined as “the degree to which individuals have the knowledge, ability, and confidence to find and evaluate information about health plans, select the best plan for their own (or their family's) financial and health circumstances, and use the plan once enrolled.” 14 To date, there is only one validated measure of health insurance literacy, the Health Insurance Literacy Measure (HILM). 8 , 15 Researchers have documented negative outcomes associated with poor health insurance literacy, such as delaying or avoiding care, 15 , 16 difficulty paying medical bills 17 , 18 and reporting difficulty in paying for non‐medical needs (e.g., rent, food). 19 National data suggest that 53.8% of US adults have low health insurance literacy based on the HILM (defined as having a score of ≤60 out of 84), 20 suggesting opportunities for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, men having higher odds of having ACSCs may be associated with their use of health services. Prior research has discussed men's underutilization of health services and factors related to their use [16][17][18] . Furthermore, research has discussed men with chronic conditions having lower confidence in taking actions to prevent symptoms for their health and knowing when to get medical care 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Two factors impacting health insurance use are confidence in understanding health coverage and satisfaction in using it. Previous research has shown that some US adults have lower confidence in understanding their health insurance use (Dean et al, 2020). Moreover, research shows lower satisfaction with private health insurance among US populations (McLeod et al, 2002).…”
mentioning
confidence: 99%
“…These higher costs are an issue because lower-wage earners with ACSCs have higher hospitalizations than higher-wage earners (Agency for Healthcare Research and Quality, 2016). Therefore, these health care costs potentially affect out-of-pocket expenses incurred by lower-wage earners (Dean et al, 2020).…”
mentioning
confidence: 99%